Aggiornamento ou fumaça de Satanás: interpretações sobre o Concílio Vaticano II no catolicismo brasileiro - Silva Júnior, Alfredo Moreira da (2013)
The Second Vatican Council represented the greatest event of the Church in the twentieth century and caused changes and effects that extend to the present. The documents produced by this event has been over time, the object of discussion between conservatives and progressives, whether of the clergy or the laity. The historical context which the announcement occurred, preparation, realization and reception of the Council, may somehow contribute to a better understanding of the course of events, the scope and purpose of this event either at European level, either in Latin American or Brazilian. In the latter case, the need for changes and adaptation of the Church to the "new times", was accompanied by a growing tension between the Church and the military regime, which, somehow, became the preferential option for the poor on a flag not only pastoral but also politics. However, the council was not perceived the same way by different interest groups inside the church, and this thesis seeks to demonstrate exactly how such antagonistic interpretations of the same event occurred. To make possible such intent, we used the concepts of representations proposed by Chartier and "the world of the text and the reader's world" _ present in the hermeneutics proposal of Ricoeur